A Case of Glomangiopericytoma at the Nasal Septum - Anzai, Takashi (Head Neck Pathol, 2017)
Glomangiopericytoma (GPC) is a rare sinonasal perivascular tumor that accounts for < 0.5–1% of all sinonasal tumors. GPC is categorized as a low-grade neoplasm with borderline malignancy and a tendency of local recurrence. GPC is a rare mesenchymal neoplasm characterized by the perivascular proliferation of tumor cells, and it requires being distinguished from solitary fibrous tumors. Here, we report a case of GPC in a 68-year-old male patient who presented at the emergency room of our hospital with a complaint of sudden epistaxis. A small, reddish, protruding tumor was observed on the right nasal septum. A biopsy revealed a possible perivascular tumor such as a GPC or solitary fibrous tumor. Thus, we performed complete resection with endoscopic surgery. The size of the resected tumor was 12 × 5 mm, and it showed a uniform proliferation of oval-to-short spindle-shaped cells with slightly branching vascular structures. The tumor cells showed minimal cytologic atypia and there were an average of 3 mitoses in 10 high power fields. Necrosis was not observed. The tumor cells showed strong and diffuse nuclear immunostaining with beta catenin and were negative with STAT6, CD34 and bcl-2. The MIB-1 labeling index was approximately 5%. Genetic testing revealed CTNNB1 mutation (p.S33C). Thus, a diagnosis of low grade GPC was made on the biopsy and the patient could be successfully treated with endoscopic resection.